Structural transfomation in employment and productivity : what can Africa hope for? - Fox, Louise; Thomas, Alun H; Haines, Cleary; International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2017)
This paper provides the most complete analysis of the structural transformation among low- and low-middle-income countries in sub-Saharan Africa to date.
1. Output, demographic, and employment transformation in Sub-Saharan Africa and Asia -- 2. Transformation and productivity: comparison with Asia -- 3. Projecting output, employment, and productivity forward through 2020 -- 4. Conclusion
Includes bibliographical references (pages 31-32)
Keywords: Labour force; EMPLOYMENT; INDUSTRIAL PRODUCTIVITY; STRUCTURAL ADJUSTMENT; AFRICA; Africa, Sub Saharan